BIOCIDAS: UM OLHAR AO PARAQUAT - GOERGEN SCHÖFFEL , EMANUEL; GÖTTENS FOLETTO , EDUARDO; LAÍS TURRA , AMANDA; LEAL DE CARVALHO , NATHÁLIA (Salão do Conhecimento, 2020)
Trabalho desenvolvido na disciplina de Toxicologia e Receituário Agronômico - Agronomia/UNIJUÍ